2020
DOI: 10.3390/jcm9082659
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Sarcopenia Assessment upon Hospital Admission to Internal Medicine Predicts Length of Hospital Stay and Re-Admission: A Prospective Study of 980 Patients

Abstract: Background: Frailty and sarcopenia are associated with frequent hospitalizations and poor clinical outcomes in geriatric patients. Ascertaining this association for younger patients hospitalized in internal medicine departments could help better prognosticate patients in the realm of internal medicine. Methods: During a 1-year prospective study in an internal medicine department, we evaluated patients upon admission for sarcopenia and frailty. We used the FRAIL questionnaire, blood alanine-amino transferase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Further, in a large prospective multicenter cohort study, 37 MAMC was not associated with longer LOS (OR = 0.98; 95% CI, 0.96–1.01) or 30 days readmission (OR = 0.98; 95% CI, 0.95–1.01). In agreement with our results, Anani et al 38 prospectively assessed 980 individuals and demonstrated that MAMC values were not correlated with patients’ LOS or risk for 30 days readmission.…”
Section: Discussionsupporting
confidence: 92%
“…Further, in a large prospective multicenter cohort study, 37 MAMC was not associated with longer LOS (OR = 0.98; 95% CI, 0.96–1.01) or 30 days readmission (OR = 0.98; 95% CI, 0.95–1.01). In agreement with our results, Anani et al 38 prospectively assessed 980 individuals and demonstrated that MAMC values were not correlated with patients’ LOS or risk for 30 days readmission.…”
Section: Discussionsupporting
confidence: 92%
“…We screened 14,006 abstracts and 2287 full texts, from which 45 cohorts (n = 39,041,266 admissions, 49 publications) 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 were eligible for inclusion ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Alanine transaminase (ALT), which is abundant in the liver and facilitates the conversion of pyruvate to the amino acid alanine, is an accessible and inexpensive biochemical assay that primarily monitors cellular and hepatic damage in the clinical setting. On the other hand, when the liver parenchyma is intact, ALT plasma levels are a good marker of systemic skeletal muscle mass and muscle strength [109]. Low ALT has also been reported to be a surrogate marker of malnutrition [80], and numerous studies accumulated the evidence that lower ALT levels may be reliable markers of sarcopenia and frailty in a variety of populations [110,111].…”
Section: Aminotransferasementioning
confidence: 99%